The Effect of Rivaroxaban on CYP4F2 and Transcription Factors’ Activity in HUVECs - Ieva Ciapiene; Vacis Tatarunas; Agne Giedraitiene; Vaidotas Zvikas; Valdas Jakstas; Audrone Veikutiene; Ugne Meskauskaite; Ugne Venckyte; Audrius Pukalskas; Vaiva Lesauskaite (Applied Sciences, 2021)
Interindividual variabilities between patients taking the anticoagulant rivaroxaban are a result of hepatic metabolism by CYP 450 enzymes. The objective of this study was to evaluate the impact of rivaroxaban on CYP4F2 and transcription factors’ activity in HUVECs. Rivaroxaban and its metabolites were detected by UPLC-ESI-MS and UPLC-QTOF-MS. CYP4F2, HNF4α, PXR and CAR expressions were determined in HUVECs by qPCR; CYP4F2 protein concentration was determined by ELISA. Rivaroxaban metabolites (M-1, M-2, M-5, M-8, M-10, M-11 and M-18) were detected in endothelial cells’ culture medium. Increasing concentrations of rivaroxaban determined lower 13-docosenamide concentrations. Rivaroxaban and dexamethasone reduced the expression of CYP4F2 when hsa-miR-24-3p—both CYP4F2 expression and CYP4F2 protein levels in HUVECs. The expression of the transcription factors HNF4α, PXR and CAR was not detected in HUVECs.